The Key Stakeholders perception of Olympic education in Iceland - Palsson, Larus Pall (Πανεπιστήμιο Πελοποννήσου, 2021)
The aim of this thesis is to explore the possibilities of expanding Olympic education in Iceland. The study illuminates the sports cultural identity of Iceland, the history of sport in Iceland from the early Vikings settlers in 9th century, through the fight for independence of the Icelandic Republic which was fought through sports events at home and in Olympic venues in the early 20th century, and soft nationalism in international sporting competitions where a population of three-hundred-fifty thousand can be an equal match to an imperial nation of millions of inhabitants. The participants are twenty-two stakeholders. Their scope of influence spans educational institutions in elementary schools, colleges, and universities as well as sports communities in clubs, Regional Sports Associations, National Sports Federations, the National Olympic and Sports Association, the National Youth Association, and the Ministry of Education, Science, and Culture and the parliament. The conclusion is that few of the key stakeholders are familiar with Olympic education, however, all perceive value education in sports as an important factor in the development of children. There is no mention of Olympic education in the educational material of sport coaches anywhere in Iceland, and neither is it mentioned in the education material of teachers or physical education teachers in universities but in this thesis are suggestions to expand the Olympic education in Iceland. The perception of Olympism is the glorious sporting moment where the spirit of the mind overcomes physical challenges. Olympism as seen by Baron Pierre de Coubertin has been preserved in the Youth Spirit of the National Youth Association founded by the first Icelandic Olympian. There is no ongoing Olympic education project in Iceland except for a few statistical and historical presentations. However, the concept of programmes including Show your character do have the same concept as Olympic education but is not named as such.
Keywords: Olympic education - Curriculum - Iceland; Olympic education - History - Iceland; Olympism; Ολυμπιακή παιδεία - Πρόγραμμα μαθημάτων - Ισλανδία; Ολυμπιακή παιδεία - Ιστορία - Ισλανδία; Ολυμπισμός; Olympic education; Viking sports; Independence sports; Sport culture; Youth spirit